Phytochemical Characterization Utilizing HS-SPME/GC-MS: Exploration of the Antioxidant and Enzyme Inhibition Properties of Essential Oil from Saudi Artemisia absinthium L. - Hanan Y. Aati; Hala A. Attia; Arwa S. Alanazi; Luluh K. AL tamran; Juergen K. Wanner (MDPI AG, 2024)
Background/Objectives: This study aimed to analyze the chemical composition and biological activities of Artemisia absinthium L. essential oil, focusing on its antioxidant and enzyme inhibition (α-amylase and urease) properties. Additionally, in vitro pharmacokinetic and pharmacodynamic evaluations were conducted through in silico molecular docking and BOILED-Egg models to assess its therapeutic potential and its potency in treating oxidative-stress-related diseases. Methods: The essential oil was isolated by the hydrodistillation (HD) of fresh plant material, and volatiles released from dried plant material were sampled via headspace solid-phase microextraction (HS-SPME), followed by a phytochemical profiling analysis through the GC-MS tool. Antioxidant capacity was assessed using DPPH, ABTS, FRAP, and nitric oxide scavenging assays, while enzyme inhibition activities were tested against α-amylase and urease. Molecular docking and BOILED-Egg models were used to evaluate compound interactions with NADPH oxidase and predict pharmacokinetic behavior, respectively. Results: HS-SPME and HD yielded 46 and 25 compounds, respectively, primarily terpenoids represented by camphor (26.4%) and cis-davanone (18.0%) in HS-SPME, while in the HD essential oil, cis-davanone (60.2%) and chamazulene (10.8%) were most prevalent. The antioxidant assays showed a strong activity, with a total antioxidant capacity of 821.8 mg ascorbic acid Eq/gm. The essential oil inhibited urease by 86.7% and α-amylase by 81.8%. Molecular docking showed strong binding affinities with NADPH oxidase, supporting the antioxidant results. Conclusions:A. absinthium EO demonstrated potent antioxidant and enzyme inhibitory activities, suggesting its therapeutic potential for treating enzyme-related disorders like diabetes mellitus and its possible use as a cure for many oxidative-stress-related diseases, thus validating the folkloric use of this plant.